Design of Tourism, Culture and Culinary Information System in Jombang Regency Based on Android - Eko Bayu Wijanarko; Siti Sufaidah; Agus Sifaunajah (SAINTEKBU, 2026)
This research aims to design and implement an Android-based digital platform to promote the tourism, culture and culinary diversity of Jombang Regency in an interactive and informative manner. The main objective is to increase the awareness of local communities and tourists of the tourism and culinary potential in Jombang through easy access to accurate and up-to-date information, as well as providing reliable guidance for tourists. In addition, this research aims to encourage local economic growth by increasing the number of tourist visits and consumption of local cultural and culinary products. Using the Rapid Application Development (RAD) method, this research includes user requirements analysis, analysis modeling, design modeling, and application construction. Through surveys, interviews, market analysis, and case studies of successful digital marketing campaigns, it is hoped that this information system can make a significant contribution in promoting and preserving cultural wealth and increasing the number of tourist visits to Jombang Regency.